Kolaborasi Teknik Insight, Modelling, Classical Conditioning sebagai Strategi Konselor dalam Pendidikan Karakter - Muhammad Misbahul Huda (Universitas Ahmad Dahlan, 2017)
This study aimed to describe the implementation of the collaboration of insight, modeling, and classical conditioning technique as the counselor’ strategy in the character building. This was a qualitative phenomenological study. This study was conducted in MA Matholi’ul Anwar Karanggeneng Lamongan. This study involved students, school counselors, and the school principal. The data were taken through observations and interviews, while the instrument of the data collection was the observation guideline and interview guideline. To analyze the data, this study employed Miles and Huberman model including the data reduction, the data presentation, and the withdrawal of conclusion. This study found that those techniques possess weaknesses and they could complete each other through collaboration. This study proved that the collaboration of insight, modeling, and classical conditioning technique play a role in students’ character building that implies the daily life.